Language Ecology or Ecolinguistics: Conceptual and Theoretical Discussions (Journal of the College of Education for Women, 2023)
Language ecology is the interactions between the environment and language. Such a discipline, ‘language ecology’ or ‘ecolinguistics has been founded by Einar Haugen’. Accordingly,  the study aims at qualitatively reviewing the theoretical and conceptual issues surrounding the subject of language ecology  by tracing the roots of language ecology. It further highlights the fundamental inconsistencies between how the concept of ecology is perceived in sociology and biology, and is applied to language, particularly, transposing the main central concepts of bio-ecology, such as relationship/interaction, environment, and organism to human language and theory of ecological-linguistic. The theory wavers among placing the focus on the organism, interrelation and the interaction. It mainly considers language ecology as a metaphor, but infrequently treats language ecology as a science field. Since the theory does not clearly delimit its object, its relationships with the neighboring scientific fields have been undecided. Moreover, the grand scope of the theories includes severe challenges in the empirical research that are limited to available resources and time. The principle, holistic, dynamic and multi-faceted perception of ecolinguistics forms a valuable correction to linguistic approaches, focusing only on language as a synchronically, static, and autonomous, quasi-invariable system. environment, and organism to human language and theory of ecological-linguistic. The theory wavers among placing the focus on the organism, interrelation and the interaction. It mainly considers language ecology as a metaphor, but infrequently treats language ecology as a science field. Since the theory does not clearly delimit its object, its relationships with the neighboring scientific fields have been undecided. Moreover, the grand scope of the theories includes severe challenges in the empirical research that are limited to available resources and time. The principle, holistic, dynamic and multi-faceted perception of ecolinguistics forms a valuable correction to linguistic approaches, focusing only on language as a synchronically, static, and autonomous, quasi-invariable system.